2019
DOI: 10.1344/der.2019.36.207-222
|View full text |Cite
|
Sign up to set email alerts
|

What’s up with transmedia and education? A literature review

Abstract: In the last few years, several works have emerged focusing on the cultural change that has to do with the simultaneous and sequential coexistence between different media. This is what is being called transmedia, and it is related to the new concepts of media convergence and participatory culture. All this new mediatic and cultural movement, of course, begins to have an echo in the educational world. However, what do we mean by this concept from an educational perspective? Through a systematic literature review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
0
11
0
8
Order By: Relevance
“…'Transmedia' as a new concept has recently been described in certain publications. One of the newest studies "through a systematic literature review" analyse a contemporary "ransmedia concept in three meanings: transmedia as an ability or literacy necessary to actively evolve in the movement of participatory culture; transmedia as a product resulting from that sequential jump between different analogical and digital media, conveyed by a narrative; and, lastly, transmedia as a didactic strategy that explores the narrative that is developed by different means to accomplish specific didactic objectives" (González-Martínez et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…'Transmedia' as a new concept has recently been described in certain publications. One of the newest studies "through a systematic literature review" analyse a contemporary "ransmedia concept in three meanings: transmedia as an ability or literacy necessary to actively evolve in the movement of participatory culture; transmedia as a product resulting from that sequential jump between different analogical and digital media, conveyed by a narrative; and, lastly, transmedia as a didactic strategy that explores the narrative that is developed by different means to accomplish specific didactic objectives" (González-Martínez et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…En la sociedad red (Castells, 2009) necesitamos establecer estructuras red, locales y globales, de colaboración abierta entre sociedad, investigación, educación e innovación en ecosistemas que, con una perspectiva de cambio para la mejora social, promuevan la creación de experiencias de enseñanza y aprendizaje situadas en nuevos contextos, superando los modelos tradicionales basados en la instrucción entendida como mera transmisión de contenidos (Álvarez-Arregui, 2019). Avanzar en esta exploración permitirá dejar atrás definitivamente el debate propio del anterior siglo, el XX, acerca de los opuestos entre aprendizaje presencial-offline y virtual-online, incorporando experiencias y trayectorias de aprendizaje como marco para la nueva actuación educativa (Esteban-Guitart et al, 2018;Gee y Esteban-Guitart, 2019 Los nuevos modelos pedagógicos tienen que estar preparados para hacer frente a escenarios de elevada complejidad e incertidumbre (Iglesias et al, 2020) dando soporte, mediante evidencias, para desarrollar experiencias expandidas, flexibles y distribuidas en torno a una narrativa transmedia a través de la cual profesores y estudiantes naturalicen la cultura digital en lo que a oportunidades y procesos de aprendizaje se refiere (González-Martínez et al, 2019). Concretamente en el contexto de la educación superior, la personalización educativa, que no pretende ser un mero proceso de individualización (customización), persigue incorporar la libertad, control y responsabilidad (agencia) de los aprendices, haciéndoles partícipes de la coordinación de los procesos de aprendizaje para convertirlos en proyectos o misiones personales que facilitarían aprendizajes con sentido y valor personal (Coll, 2018;Coll, Esteban-Guitart e Iglesias, 2020;Jubany, 2012).…”
Section: Extracto 3 Comentarios Recogidos En Las E Ncuestas De Satisfacción De Las Y Los Estudiantesunclassified
“…La convergencia así entendida tendría que ver con el flujo de contenidos entre diferentes medios y lo que hace la audiencia para disfrutar con aquellas experiencias de entretenimiento que le atraen, propiciando la aparición de nuevas narrativas que se despliegan a través de múltiples medios y plataformas y que conocemos como transmedia (González-Martínez et al, 2019).…”
Section: Introductionunclassified
“…As already highlighted above, not only transmedia has an important echo in general (from a media perspective) but also from an educational perspective. According to that, a couple of years ago, the different approaches that the concept could have in the context of learning were analysed [7]. This study concluded that, in the educational field, transmedia could be understood as a media product, as a cultural phenomenon for which subjects require special literacies or as a new way of understanding the design of teaching-learning experiences.…”
Section: Theoretical Frameworkmentioning
confidence: 99%